2019
DOI: 10.1515/med-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

The pseudogene PTTG3P promotes cell migration and invasion in esophageal squamous cell carcinoma

Abstract: AbstractPseudogenes are pivotal funtional non-coding RNAs in tumorigenesis. Cumulative evidences have shown that pituitary tumor-transforming 3, pseudogene (PTTG3P), serves as an oncogene in multiple human cancers. However, its expression pattern, biological function, and potential targets in esophageal squamous cell carcinoma (ESCC) remain unknown. Here, by quantitative real-time polymerase chain reaction (qRT-PCR) in 50 cases of ESCC, we found that the expression of PTTG3P, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The PTTG gene family consists of three members: one pseudogene ( PTTG3P ) and two protein coding genes, namely PTTG1 and PTTG2 [ 12 ]. Numerous studies have proven the significant role of PTTGs in cancer initiation and progression [ 11 , 13 , 16 , 17 , 18 ], although the mechanisms of these processes mostly remain unclear. It is known that PTTG3P influences tumor growth and metastasis in both cervical cancer and hepatocellular carcinoma [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The PTTG gene family consists of three members: one pseudogene ( PTTG3P ) and two protein coding genes, namely PTTG1 and PTTG2 [ 12 ]. Numerous studies have proven the significant role of PTTGs in cancer initiation and progression [ 11 , 13 , 16 , 17 , 18 ], although the mechanisms of these processes mostly remain unclear. It is known that PTTG3P influences tumor growth and metastasis in both cervical cancer and hepatocellular carcinoma [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coexisting expression of PTTG1 and PTTG2 genes with the PTTG3P pseudogene may suggest that PTTG3P regulates PTTG1 and PTTG2 . It is possible that PTTG3P positively promotes the regulation of parental genes PTTG1 and PTTG2 , as is the case in esophageal squamous cell carcinoma [ 16 ]. In vitro studies have confirmed that exogenously the overexpression of PTTG3P promotes the transcription of its parental genes PTTG1 and PTTG2 in esophageal squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations